Direct contact membrane distillation for the concentration of clarified orange juice. (October 2016) - Quist-Jensen, C.A.; Macedonio, F.; Conidi, C.; Cassano, A.; Aljlil, S.; Alharbi, O.A.; Drioli, E.
Abstract: Multi-stage vacuum evaporation is a conventional unit operation in the industrial production of concentrated fruit juices. Membrane processes, such as direct contact membrane distillation (DCMD) and osmotic distillation (OD), offer several advantages over the traditional thermal evaporation, since they operate at a lower temperature thus preserving the nutritional and organoleptic properties of the fresh juice. These processes involve transport of water vapor through the pores of hydrophobic membranes due to a vapor pressure driving force provided by temperature and/or solute concentration differences across the membrane. In DCMD water is used on the permeate side instead of a stripping solution, thus increasing the sustainability of the process. The aim of this study was to evaluate the potential of DCMD for concentrating clarified orange juice on laboratory scale. The raw juice was previously clarified by ultrafiltration (UF) in order to remove suspended solids and juice turbidity; the clarified juice, with an initial total soluble solids (TSS) content of about 9.5 °Brix, was pre-concentrated up to 24 °Brix and then concentrated up to 65 °Brix through a two-step DCMD process. The performance of both UF and DCMD processes was evaluated in terms of productivity and juice quality. Samples from both processes were analyzed in terms of total suspended solids, TSS, total antioxidant activity (TAA) and phenolic compounds. Concentrated samples were also analyzed in order to evaluate the presence of crystals. Experimental results indicated that, at high concentration, the transmembrane flux decay can be mainly attributed to the increasing of the juice viscosity. Moreover, analytical measurements proved that all the antioxidant compounds of the clarified orange juice are well preserved through the DCMD process. Therefore, the UF/DCMD integrated process may be used to obtain high quality concentrated juices, as in the final product the organoleptic, nutritional and antioxidant properties of the fresh juice are efficiently preserved. Highlights: An integrated UF/DCMD system was utilized for concentrating orange juice. UF and DCMD performances were evaluated in terms of flux and juice quality. The clarified juice was concentrated from 9.5 up to 65 °Brix. Analytical measurements proved that antioxidants were concentrated via MD unit. UF/DCMD process may be used to obtain high quality concentrated juices.